Current pharmacotherapy of overactive bladder - Kreydin,Evgenyi I. (2021)
ABSTRACT Overactive bladder is a symptom complex consisting of bothersome storage urinary symptoms that is highly prevalent among both sexes and has a significant impact on quality of life. Various antimuscarinic agents and the beta-3 agonists mirabegron and vibegron are currently available for the treatment of OAB. Each drug has specific pharmacologic properties, dosing schedule and tolerability profile, making it essential to individualize the medical treatment for the patient's characteristics and expectations. In this manuscript, we review the most important factors involved in the contemporary pharmacological treatment of OAB.